A temperature-pressure flexible sensor with near-zero temperature coefficient of resistance and a preparation method thereof
By fabricating a near-zero resistance temperature coefficient flexible temperature-pressure sensor, the Seebeck effect and piezoresistive effect are utilized to achieve independent responses to temperature and pressure signals, solving the problem of accurate signal monitoring under multi-physics fields in existing sensors, and improving the signal-to-noise ratio and sensor stability.
Patent Information
- Application Number
- CN202510875638.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2026-02-06
- Estimated Expiration
- 2045-06-27
AI Technical Summary
Existing flexible sensors struggle to accurately monitor stress and temperature field signals under multi-physics conditions. In particular, the accuracy of resistance signals is affected by the sensor's inherent temperature coefficient of resistance when the temperature changes, leading to complex decoupling analysis.
Using a near-zero resistance temperature coefficient sensing material, signal conversion is achieved through the Seebeck effect and piezoresistive effect. The preparation method includes preparing PDMS prepolymer, adding NaCl particles, vacuum plasma modification, and combining Ti3C2 MXene nanosheets and Nafion resin to form a temperature-pressure flexible sensor with independent response.
This technology enables independent responses of the sensor to temperature and pressure signals, avoids temperature interference with the resistance signal, improves the signal-to-noise ratio, and enhances the sensor's service stability and cyclic loading-unloading capability.
Smart Images

Figure CN120760900B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of multifunctional sensor preparation, and particularly relates to a temperature-pressure flexible sensor with near-zero resistance temperature coefficient and a preparation method thereof. BACKGROUND
[0002] With the rapid development of aerospace, rail transportation and civil machinery engineering fields, the long-period safe service of key engineering components has increasingly become the focus of the industry. Implementing structural health monitoring of such key engineering components is one of the effective strategies to ensure their safe service. Flexible sensors have attracted widespread attention from researchers in the field of structural health monitoring due to their excellent shape adaptability. Engineering components often serve in environments with multiple field coupling such as stress field, temperature field, force field and magnetic field. Accurate identification and detection of multiple physical field signals are the development direction of flexible sensors for structural health monitoring. However, existing flexible sensors often have the problem of affecting the accurate output of signals under the action of multiple physical fields, and accurate monitoring of multiple signals is the key to correctly evaluating the structural health of engineering components by flexible sensors.
[0003] For long-term service of engineering structural components such as autoclaves, industrial boilers and transportation pipelines, it is necessary to accurately monitor the stress field and temperature field signals at the same time. For this purpose, people have developed various temperature-pressure flexible sensors, among which the most widely used are resistance-type sensors that couple pressure and temperature variables. However, the output resistance signal needs to be decoupled and analyzed during use, and the algorithm decoupling must rely on the accuracy of the model, which undoubtedly increases the difficulty of researchers' work; the multifunctional sensor prepared by compounding the sensing material with thermoelectric effect and piezoresistive effect and the flexible matrix can produce resistance and voltage signal responses to external pressure and temperature stimulation. The decoupling process of single resistance signal output is effectively avoided. However, the sensor based on the resistance-pressure principle to identify the stress field changes will be affected by the inherent resistance temperature coefficient of the sensor when it is in a changing temperature environment, and the development of temperature-pressure flexible sensors with near-zero resistance temperature coefficient (the resistance value of the material changes very little with temperature, close to zero) can effectively solve this problem. SUMMARY
[0004] The purpose of the present application is to provide a temperature-pressure flexible sensor with near-zero resistance temperature coefficient and a preparation method thereof. The prepared sensor has a sensing material with a near-zero resistance temperature coefficient of -0.000836% ℃ -1 , and realizes signal conversion through the Seebeck effect and piezoresistive effect, thereby realizing independent response to temperature and pressure signals during the service process of engineering structures.
[0005] The technical scheme of the present application is:
[0006] A preparation method of a near-zero resistance temperature coefficient temperature-pressure flexible sensor, the specific process is as follows:
[0007] (1) Configure PDMS prepolymer, then add NaCl particles and stir uniformly, place the foregoing mixture in vacuum for degassing, take out and compact, and solidify under vacuum;
[0008] (2) Place the sample after solidification in water and heat to dissolve NaCl particles, and then dry;
[0009] (3) Perform vacuum plasma modification on the sample obtained in step (2);
[0010] (4) Place the modified sample in a Ti3C2 MXene nanosheet aqueous dispersion and mix uniformly;
[0011] (5) Add perfluorosulfonic acid resin (Nafion resin) to the mixed solution, stir and react, and then dry to obtain a composite sponge block;
[0012] (6) Paste metal electrodes on the upper and lower surfaces of the composite sponge block through conductive adhesive.
[0013] Further, the mass ratio of NaCl particles to PDMS prepolymer in step (1) is 1:6-1:8; the PDMS prepolymer is prepared by mixing PDMS (polydimethylsiloxane) and a curing agent in a mass ratio of 8:1-10:1; and the particle size of NaCl particles is 25-350 μm.
[0014] Further, the absolute pressure value during vacuum standing and degassing in step (1) is 1-2 kPa, and the degassing time is 3-5 h; the absolute pressure value during solidification under vacuum is 1-2 kPa, the solidification temperature is 80-100℃, and the solidification time is 3-5 h.
[0015] Further, the heating in step (2) is water bath heating, and the temperature is 80-100℃; the drying temperature is 60-85℃; after drying, the PDMS sponge body is cut to obtain a PDMS sponge body, and the size of the PDMS sponge body is a cuboid with a size of 5-10 mm x 5-10 mm x 4-6 mm.
[0016] Further, the size of the cubic cavity of the PDMS sponge body is 25-350 μm.
[0017] Further, the plasma modification conditions in step (3) are as follows: the oxygen flow rate is 2-3 L / min, the power is 80-120 W, and the cleaning time is 15-40 s.
[0018] Further, the mass concentration of the Ti3C2 MXene nanosheet in the Ti3C2 MXene nanosheet aqueous dispersion solution in step (4) is 2 mg / mL to 3 mg / mL, the volume of the Ti3C2 MXene nanosheet aqueous dispersion solution is 500 mL to 1000 mL, and the PDMS sponge body needs to be immersed.
[0019] Further, the mass ratio of the Nafion resin to the Ti3C2 MXene in step (5) is 5:7 to 5:28; the reaction time is 24 to 72 h; the drying temperature is 60 DEG C to 85 DEG C, and the drying time is 2 to 5 h.
[0020] Further, the conductive adhesive in step (6) is a conductive silver paste or a conductive aluminum paste, and the metal electrode is a copper foil electrode; the metal electrode is a rectangular structure with a certain thickness, and the plane size of the rectangle is greater than or equal to the surface size of the sponge block body in contact with it, and the thickness is 20 to 50 mu m.
[0021] A temperature-pressure flexible sensor with near-zero resistance temperature coefficient prepared by the preparation method of the present application realizes monitoring of external temperature and stress through the Seebeck effect and the piezoresistive effect, and the sensor shows a near-zero resistance temperature coefficient of -0.000836% DEG C -1 and a Seebeck coefficient of up to 0.0918 mV / K.
[0022] The present application has the advantages of:
[0023] (1) The temperature-pressure flexible sensor prepared by the present application uses a sensing material with a near-zero resistance temperature coefficient of -0.000836% DEG C -1 , which avoids the interference of ambient temperature on the piezoresistive signal during monitoring of the temperature and pressure response of the engineering component;
[0024] (2) The temperature-pressure flexible sensor prepared by the present application uses a material with a high Seebeck coefficient of up to 0.0918 mV / K, which makes the sensor have a super-high signal-to-noise ratio in the monitoring of the service temperature of the engineering component;
[0025] (3) The temperature-pressure flexible sensor prepared by the present application monitors the service temperature of the measured engineering component through the Seebeck effect, and monitors the stress on the measured engineering component through the piezoresistive effect, and the voltage and resistance signals monitored are not interfered with each other, realizing the independent decoupling function of the sensor;
[0026] (4) The temperature-pressure flexible sensor prepared in the application uses PDMS as a flexible matrix, the surface of the sponge is modified by plasma modification technology, the modified sponge surface is combined with Ti3C2 MXene nanosheets through electrostatic attraction, and the introduction of the conductive Nafion resin solution crosslinking agent further enhances the adhesion of the Ti3C2 MXene nanosheets on the sponge surface, greatly enhancing the service stability of the sensor, so that the sensor exhibits a cycle loading-unloading stability of up to 11000 times. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 The preparation process of the temperature-pressure flexible sensor of the application.
[0028] Figure 2 The relative resistance change curve of the temperature-pressure flexible sensor of Example 1 of the application in the temperature change process.
[0029] Figure 3 The thermoelectric voltage change curve of the temperature-pressure flexible sensor of Example 1 of the application under different temperature gradients: (a) is the actual change curve; (b) is the fitting curve.
[0030] Figure 4 The resistance change curve of the temperature-pressure flexible sensor of Example 1 of the application under different pressures: (a) is the resistance signal response linear fitting graph in the working range of 0-100kPa; (b) is the relative resistance change curve in the dynamic compression-release process under different pressures.
[0031] Figure 5 The sensor resistance and voltage signal response curve of the temperature-pressure flexible sensor of Example 1 of the application under the action of load and temperature stimulation.
[0032] Figure 6 The relative resistance change curve of the sensor prepared in the application in the process of pressure stimulation cycle loading and unloading 11000 times: (a) the sensor prepared in Example 1; (b) the control group sensor prepared in Comparative Example 1. DETAILED DESCRIPTION
[0033] The application will be described in detail below with reference to the drawings and examples.
[0034] Example 1
[0035] As shown in Figure 1 , the preparation method of the temperature-pressure flexible sensor with near-zero resistance temperature coefficient is as follows:
[0036] (1) PDMS (polydimethylsiloxane) and its curing agent (Dow Corning: Sylgard 184) were prepared into a PDMS prepolymer with a mass ratio of 10:1, and stirred and mixed uniformly. NaCl analytical pure particles (particle size: 25-350 μm) were added to the PDMS prepolymer, with a mass ratio of NaCl to PDMS prepolymer of 1:7, and stirred uniformly before being poured into a polytetrafluoroethylene mold with an inner diameter of 6.5 cm. Then, after standing at room temperature for 5 hours in a vacuum (absolute pressure value: 1.325 kPa) environment to eliminate bubbles, the sample was removed, compacted in the mold, and then placed in a vacuum (absolute pressure value: 1.325 kPa) environment at 80°C for 4 hours to solidify, and then removed and cooled to room temperature in air;
[0037] (2) The above sample was placed in 500 mL of water (the sample was submerged in water), and the NaCl particles were dissolved in an 80°C water bath. Then, the PDMS sponge body with a pore size of 25-350 μm was obtained by drying at 80°C, and was cut into a 10 mm x 10 mm x 5 mm cube;
[0038] (3) The above cut PDMS porous sponge block was placed in the cavity of a vacuum plasma cleaning machine (Nanen Technology, NE-Q05), with a working power of 100 W and a cleaning time of 20 s, and oxygen was introduced (oxygen flow: 2 L / min). The high-energy particles (O + , O2 + ) generated by the ionization of oxygen in the cavity formed positively charged polar groups on the surface of the material under continuous bombardment by high-energy particles.
[0039] (4) The above modified PDMS porous sponge block was placed in a 200 mL (the dispersion liquid should cover the sponge block) Ti3C2 MXene nanosheet (lateral size: 1-3 μm) aqueous dispersion liquid with a concentration of 2-3 mg / mL (specifically 2 mg / mL), and the positively charged surface of the modified sponge block combined with the negatively charged Ti3C2 MXene nanosheet through electrostatic attraction;
[0040] (5) Then, Nafion resin (Macklin: Nafion resin 118) was added in a mass ratio of 5:7 with Ti3C2 MXene, and the combined sponge block was removed after stirring for 24 hours, and was dried at 85°C under vacuum (absolute pressure value: 1.325 kPa) for 3 hours;
[0041] (6) The upper and lower surfaces of the above-mentioned composite sponge block were pasted with copper foil electrodes (copper foil electrode size: 10 mm x 10 mm x 0.025 mm) through conductive silver paste (SPI#05001-AB) to prepare a temperature-pressure flexible sensor with near-zero resistance temperature coefficient.
[0042] The temperature-pressure flexible sensor prepared in this example can independently perceive pressure and temperature stimuli, and convert temperature and pressure stimuli into voltage and resistance signals through the Seebeck effect and piezoresistive effect, respectively. Figure 2 Figure (a) is a relative resistance change curve of the temperature-pressure sensor of the present application during temperature change. The results show that within a certain temperature change range, the sensor exhibits a near-zero resistance temperature coefficient of -0.000836% ℃ -1 The influence of temperature change on the resistance output signal can be effectively eliminated. Figure 3 Figure (a) is a thermoelectric voltage change curve of the temperature-pressure flexible sensor of the present application under different temperature gradients. As can be seen from the figure, the thermoelectric voltage increases with the increase of the temperature gradient, and within the temperature difference range of 5K-30K, it shows a stable increasing trend. Figure 3 Figure (b) is a fitting curve of the thermoelectric voltage and temperature gradient change of the temperature-pressure flexible sensor of the present application. From the fitting results, it can be known that the Seebeck coefficient of the sensor is as high as 0.0918 mV / K and has extremely high linearity (R 2 = 0.999) within the temperature difference range of 5K-30K. Figure 4 Figure (a) is a linear fitting graph of the resistance signal response of the temperature-pressure flexible sensor of the present application within the working range of 0-100 kPa. As can be seen from the figure, the sensor responds linearly in three sections, and has extremely high linearity in each section. Figure 4 Figure (b) is a relative resistance change curve of the sensor during the dynamic compression-release process under different pressures. It can be seen that the sensor can output stable resistance signals during the dynamic compression-release process under different pressures. Figure 5 Figure (a) is a resistance and voltage signal response curve of the sensor under the pressure and temperature stimuli provided by the heating table (ΔT = 5K) and the weight (2g) within the test time period of 20s-40s, and under no pressure and temperature stimuli during the rest of the test time. The voltage and resistance signal responses can be generated at the same time when the pressure and temperature changes are applied to the sensor.
[0043] Comparative Example 1
[0044] The preparation process is the same as that of Example 1, except that in step (5), no Nafion resin is added, and the mixture obtained in step (4) is directly stirred for 24 hours. Then, the compounded sponge block is taken out and vacuum dried at 85°C for 3 hours.
[0045] Figure 6 (a) is the relative resistance change curve of the sensor prepared in Example 1 during the process of cyclic loading and unloading of pressure stimulation for 11000 times. It can be seen that the resistance change remains in the same amplitude without obvious deviation, indicating that the sensor has excellent cycle stability in dynamic pressure change (0-60 kPa). Figure 6 (b) is the relative resistance change curve of the control sensor prepared in Comparative Example 1 during the process of cyclic loading and unloading of pressure stimulation for 7000 times. It can be seen that the amplitude of resistance change of the control sensor has obvious fluctuation, and the control sensor can only withstand the process of cyclic loading and unloading of pressure stimulation for 7000 times in dynamic pressure change (0-40 kPa), further proving that the introduction of the crosslinking agent of Nafion resin solution enhances the service stability of the sensor.
Claims
1. A method of making a near-zero temperature coefficient of resistance temperature-pressure flexible sensor, characterized by: The specific process is as follows: (1) configure the PDMS prepolymer, then add NaCl particles and stir uniformly, place the above mixture in vacuum for degassing, take out and compact, and solidify under vacuum; the mass ratio of the NaCl particles to the PDMS prepolymer is 1:6-1:8; the PDMS prepolymer is prepared by mixing polydimethylsiloxane (PDMS) and a curing agent in a mass ratio of 8:1-10:1; the particle size of the NaCl particles is 25-350 μm; (2) place the solidified sample in water and heat to dissolve the NaCl particles, and then dry; (3) vacuum plasma modify the sample obtained in step (2); the plasma modification conditions are as follows: the oxygen flow rate is 2-3 L / min, the power is 80-120 W, and the cleaning time is 15-40 s; (4) mix the modified sample in a Ti3C2 MXene nanosheet aqueous dispersion; the mass concentration of the Ti3C2 MXene nanosheets in the Ti3C2 MXene nanosheet aqueous dispersion is 2-3 mg / mL, the volume of the Ti3C2 MXene nanosheet aqueous dispersion is 200-500 mL, and the PDMS sponge body is immersed; (5) add Nafion resin to the mixed solution, stir and react, and then dry to obtain a composite sponge block; the mass ratio of the Nafion resin to the Ti3C2 MXene in the mixed solution is 5:7-5:28; the reaction time is 24-72 h; the drying temperature is 60-85℃, and the drying time is 2-5 h; (6) paste metal electrodes on the upper and lower surfaces of the composite sponge block by using conductive adhesive.
2. The method of claim 1, wherein: In step (1), the absolute pressure value during the vacuum degassing is 1-2 kPa, and the degassing time is 3-5 h; the absolute pressure value during the vacuum solidification is 1-2 kPa, the solidification temperature is 80-100℃, and the solidification time is 3-5 h.
3. The method of claim 1, wherein: In step (2), the heating is water bath heating, and the temperature is 80-100℃; the drying temperature is 60-85℃; after drying, the PDMS sponge body is cut into a cuboid with a size of 5-10 mm×5-10 mm×4-6 mm.
4. The method of claim 3, wherein: The size of the cubic cavity of the PDMS sponge body is 25-350 μm.
5. The method of claim 1, wherein: In step (6), the conductive adhesive is conductive silver paste or conductive aluminum paste, and the metal electrode is a copper foil electrode; the metal electrode has a rectangular structure with a certain thickness, and the size of the plane of the rectangle is greater than or equal to the size of the surface of the sponge block in contact with it, and the thickness is 20-50 μm.
6. A near-zero resistance temperature coefficient temperature-pressure flexible sensor prepared according to the method of any one of claims 1-5, characterized in that: The temperature-pressure flexible sensor realizes monitoring of external temperature and stress through Seebeck effect and piezoresistive effect, and the sensor shows a near-zero resistance temperature coefficient of -0.000836% °C -1 and a Seebeck coefficient of up to 0.0918 mV / K.
Citation Information
Patent Citations
MXene@CS@PDMS three-dimensional porous composite material and preparation method and application thereof
CN110375894A
Method for detecting seawater-based zinc ions based on graphene-nano cerium oxide modified electrode
CN116698936A